Aquatic organisms modulate the bioreactivity of engineered nanoparticles: focus on biomolecular corona - Liu, Wei; Worms, Isabelle A. M.; Jakšić, Željko; Slaveykova, Vera I. (Frontiers in Toxicology, 2022)
The increased use of nanoparticle (NP)-enabled materials in everyday-life products have raised concerns about their environmental implications and safety. This motivated the extensive research in nanoecotoxicology showing the possibility that NPs could cause harm to the aquatic organisms if present at high concentrations. By contrast, studies dealing with influence that organisms could exert on the fate and thus effects of NPs are still very rare. Drawing on the existing up-to-date knowledge we critically discuss the formation of biomolecular corona as one of the mechanisms by which organisms exerted control on the NPs fate in the aquatic and biotic environments. We focused the formation of corona by exogeneous and endogenous biomolecules and illustrated the discussion with the specific example of phytoplankton and aquatic invertebrate species. We highlighted the necessity to incorporate the concept of biomolecular corona within more general framework considering the feedback of aquatic organisms and the control they exert in shaping the fate and impact of NPs in the aquatic and biological environment. In our view such broader perspective will contribute to get novel insights into the drivers of environmental transformations of NPs and their mechanisms, which are important in environmental risk assessment.